ANALISIS AISAS MODEL TERHADAP “BTS EFFECT” SEBAGAI BRAND AMBASSADOR DAN INFLUENCER - LINA SINATRA WIJAYA; VIRGINIA - - (Jurnal Komunikasi, 2020)
BTS, is the most famous Korean idol group band boy currently not only in Indonesia but also around the world. It has become the target of many big companies to cooperate with them as the Brand Ambassadors or  Influencers of their company products because of the huge benefits they can receive that eventually lead to the term "Bts Effect" . This study aims to analyze the AISAS model towards the BTS Effects as the brand ambassador/influencer. It is qualitative research which uses structured Questionnaires and observation for gaining the data. The target of this study is 25 informants as BTS lovers who have used BT21 products.  The result of this study showed that in this digital era, AISAS model is more suitable to be implemented in the marketing promotion process. By applying this model, customer motivation will increase, and this will encourage them to buy the product. Besides that, it will also create positive customer behavior towards the products